Tumor regression after neoadjuvant chemotherapy in locally advanced colon cancer - A. O. Rasulov; V. M. Kulushev; V. S. Ananiev; M. Yu. Fedyanin; N. A. Kozlov (Тазовая хирургия и онкология, 2015)
Background. Our aim was to investigate efficacy of neoadjuvant chemotherapy in colon cancer based on tumor regression.Materials and methods. This retrospective study included colon cancer patients, who underwent treatment at the department of oncoproctology of Russian N. N. Blokhin Cancer Research Center during 2007–2014 and who received a minimum of 2 cycles of neoadjuvant chemotherapy. Primary endpoint was tumor regression. Tumor regression was analyzed separately considering treatment scheme, number of treatment cycles and presence of lymph node metastases.Results. 18 patients were included (9 male and 9 female). 9 patients had locally advanced T4N0–2M0 colon cancer and 9 patients had metastatic T3–4N0–2M1 colon cancer. 17 (94.4 %) patients had macroscopic signs of residual tumor. Grade 1 and 2 tumor regression(Dworak) was observed in 6 (33.3 %) and 10 (55.5 %) patients respectively. 2 (11.1 %) patients had no signs of tumor regression. Grade 2 tumor regression was most frequently (in 6/10 patients) observed after XELOX or FOLFOX chemotherapy.Conclusions. Neoadjuvant chemotherapy leads to tumor regression inn most colorectal cancer patients. In our group chemotherapy regimens including oxliplatin were more effective.